2011
DOI: 10.2337/dc10-1680
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Plasma Glucose and Hemoglobin A1c in Identifying and Predicting Diabetes

Abstract: OBJECTIVETo compare fasting plasma glucose (FPG) and HbA1c in identifying and predicting type 2 diabetes in a population with high rates of diabetes.RESEARCH DESIGN AND METHODSDiabetes was defined as an FPG level ≥126 mg/dL or an HbA1c level ≥6.5%. Data collected from the baseline and second exams (1989–1995) of the Strong Heart Study were used.RESULTSFor cases of diabetes identified by FPG ≥126 mg/dL, using HbA1c ≥6.5% at the initial and 4-year follow-up diabetes screenings (or in identifying incident cases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 25 publications
2
41
1
Order By: Relevance
“…Results of the EPIC-Potsdam Study also suggested that risk reclassification was improved by adding FPG (IDI 0.0553) or HbA 1c (IDI 0.0974) values using the prediction model by the German Diabetes Risk Score as a reference [14]. Recent prospective studies have examined the utility of introducing HbA 1c testing for predicting diabetes [15,16,[23][24][25][26][27], and some reports have described the development of models to predict future diabetes using blood variables including FPG and HbA 1c [15,25,29]. More recently and concomitantly with the preparation of this manuscript, a risk score that concurrently included measurements of FPG, HbA 1c and other biochemical markers was reported in a Korean population [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the EPIC-Potsdam Study also suggested that risk reclassification was improved by adding FPG (IDI 0.0553) or HbA 1c (IDI 0.0974) values using the prediction model by the German Diabetes Risk Score as a reference [14]. Recent prospective studies have examined the utility of introducing HbA 1c testing for predicting diabetes [15,16,[23][24][25][26][27], and some reports have described the development of models to predict future diabetes using blood variables including FPG and HbA 1c [15,25,29]. More recently and concomitantly with the preparation of this manuscript, a risk score that concurrently included measurements of FPG, HbA 1c and other biochemical markers was reported in a Korean population [40].…”
Section: Discussionmentioning
confidence: 99%
“…Introducing HbA 1c into a prediction model has been suggested to be effective in screening for future diabetes [14][15][16][22][23][24][25][26][27][28], and a few models to predict the development of diabetes have recently been developed that concurrently include measurements of FPG, HbA 1c and other blood markers [15,25,29]. After revising the diagnostic criteria for type 2 diabetes by introducing HbA 1c in 2010 [30], the ADA published guidelines and recommendations for diagnosing diabetes based on published data or derived from expert consensus [31].…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, research on the sensitivity and specificity of HbA 1c and FPG testing for undiagnosed diabetes has been inconsistent (22)(23)(24)(25)34,35). Further, in the few studies to date that have directly compared prediabetes prevalence according to FPG and HbA 1c criteria, considerable differences between estimates have been noted, largely by finding HbA 1c (5.7-6.4% [39-48 mmol/mol]) to be a less sensitive criterion than FPG (5.6-6.9 mmol/L [or equivalently 100-125 mg/dL]).…”
Section: Discussionmentioning
confidence: 99%
“…Given recent additions to diagnostic guidelines (16) to include hemoglobin A 1c (HbA 1c ) levels, assessing the hidden burden of undiagnosed diabetes has again become particularly important. Where the measurement of FPG level is relatively simple and inexpensive to perform, HbA 1c measurement is a more convenient diagnostic technique that does not require the patient to fast and displays less day-to-day variability (14,(17)(18)(19)(20)(21)(22)(23)(24)(25). HbA 1c measurement is also attractive for opportunistic screening as it can be performed at any time of the day without prior fasting.…”
mentioning
confidence: 99%
“…Wang and colleagues 39 describe analyses of 4549 American Indian men and women. They developed a logistic model for the risk of diabetes defined according to HbA 1c ≥ 6.5% and FPG ≥ 7.0 mmol/l.…”
mentioning
confidence: 99%